2022
DOI: 10.3389/fsurg.2022.924810
|View full text |Cite
|
Sign up to set email alerts
|

Decision support by machine learning systems for acute management of severely injured patients: A systematic review

Abstract: IntroductionTreating severely injured patients requires numerous critical decisions within short intervals in a highly complex situation. The coordination of a trauma team in this setting has been shown to be associated with multiple procedural errors, even of experienced care teams. Machine learning (ML) is an approach that estimates outcomes based on past experiences and data patterns using a computer-generated algorithm. This systematic review aimed to summarize the existing literature on the value of ML fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Two recent systematic reviews compared machine learning models for predicting mortality and decision support [ 23 , 24 ]. Zhang et al [ 24 ] discussed six studies using machine learning models based on the national database.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews compared machine learning models for predicting mortality and decision support [ 23 , 24 ]. Zhang et al [ 24 ] discussed six studies using machine learning models based on the national database.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 8% of all deaths due to major (orthopaedic) trauma are considered potentially preventable ( 75 ). The connection of computer-generated stimulations through visual and auditory displays during the resuscitation can enhance trauma care professionals' interaction and might reduce faulty omission and miscommunication ( 75 ). Previous studies have shown effective tools for the prediction of injury pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Ensemble models often employ bagging, boosting or stacking approaches to combine multiple machine learners, maximising performance of the prediction model when little is known about which single learner best predicts a given outcome 32. Super Learner—a stacking-type ensemble prediction model—has been used in a variety of health outcome prediction models and is generally robust to model misspecification 33–36. Performance and architecture of Super Learner has been described elsewhere 37 38.…”
Section: Methodsmentioning
confidence: 99%
“…32 Super Learner-a stacking-type ensemble prediction modelhas been used in a variety of health outcome prediction models and is generally robust to model misspecification. [33][34][35][36] Performance and architecture of Super Learner has been described elsewhere. 37 38 Super Learner uses cross validation to evaluate and weight the performance of multiple machine learning algorithms to build one ensemble model, thus maximising efficiency while minimising predictive error.…”
Section: Prediction Modelmentioning
confidence: 99%